Research on MVB Protocol Conformance Testing and Implementation of Basic Interconnection Tests - WANG Feng-chao; SHEN Ping; YAN Xiang; WANG Li-de (机车电传动)
In order to assure compatibility and interoperability of MVB devices from different manufacturers and enhance success rate of interconnection, it was essential to carry out MVB protocol conformance testing for MVB devices. MVB protocol features and conformance testing contents were expounded. The conformance testing platform was designed and constructed according to testing requirements in lab environment, and testing programs were achieved for basic interconnection tests on the platform, which provided useful references to further conformance testing of MVB devices.